A comparative study of learning outcomes in the teaching factory and project based learning models in vocational high schools - Ruswantyo, Almira Theda Oktavia; Sohidin, Sohidin (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
There are various learning models used by schools to fulfill student learning outcomes, such as the teaching factory model and project-based learning. The aims of this study are to (1) identify the learning achievements of students from the Marketing expertise program that implements the teaching factory model in Phase F at SMK Negeri 6 Surakarta and (2) identify the learning achievements of students from the Marketing expertise program that implements the project-based learning model in Phase F at SMK Negeri 3 Surakarta. This research is a study using a qualitative descriptive method. Data for this research were obtained from interviews with marketing program teachers and students, classroom observations, and document analysis. The results of this study are as follows: first, student learning outcomes in the marketing program implementing the teaching factory learning model can be achieved and result in industrial competencies. Second, student learning outcomes in the marketing vocational program using the project-based learning model still have several competencies that have not been achieved.